Handbook of Critical Incident Analysis. - Schwester, Richard W. (Taylor and Francis, 2014)
Critical incidents all too often explode onto the social conscious and challenge our sense of security. This comprehensive handbook brings together a range of experts who provide a foundation for the field of critical incident analysis by examining specific incidents9/11, the Virginia Tech massacre, the H1N1 pandemic, the BP oil spill, and more--through various methodological and disciplinary lenses.